Interictal wave pattern study in EEG of epilepsy patients - Bhuyan, Rimpy; Jahan, Wasima; Upadhyaya, Narayan (International Journal of Research in Medical Sciences, 2017)
Background: EEG or Electroencephalogram is the most important diagnostic tool to detect Epilepsy. Interictal period is the time interval between two seizure episodes of an Epileptic patient. Certain wave patterns appear in the interictal period in the EEG which might predict the onset of a seizure or may give information about the last seizure attack. The aim of the study was to know how the interictal wave patterns help in diagnosing and classifying Epilepsy cases Methods: The present study was done in the Department of Physiology in association with the Department of Neurology, Assam Medical College and Hospital, Dibrugarh, Assam from June 2014 to May 2015. 113 clinically diagnosed cases of Epilepsy were studied and analyzed through Electro-encephalogram using the internationally accepted 10-20 electrode placement method. The interictal period was enquired in the history and the wave patterns that appeared in the EEG were recorded. The EEG findings were compared with the clinical diagnosis. Results: The IEDs detected were mainly of four types: Sharp waves, Spikes, Spike and wave and Polyspikes. It was found that the sharp waves (88.89%) were the predominant waveforms in the IEDs detected and this was followed by the ‘3 Hz spike and wave pattern’. It was also seen that the ‘3 Hz spike and wave pattern’ was associated with ‘Absence seizures’. And Myoclonic seizures were associated with polyspikes. Conclusions: It is hereby concluded that certain wave patterns in EEG appear in certain types of epilepsy that can be clinically correlated for proper diagnosis of epilepsy.